Influence of glottal closure configuration on vocal efficacy in young normal-speaking women - Schneider, Berit; Bigenzahn, Wolfgang (Journal of voice, 2003)
Posterior closure insufficiency of the glottis is often mentioned in connection with permanent voice disorders. Recently published studies have revealed that an incomplete closure of the glottis can be found also in normal-speaking voices, especially in women. However, the effect of glottal closure configuration on vocal efficacy is not sufficiently clarified. The purpose of this study was to determine the effect of glottal closure configuration on singing and speaking voice characteristics. Overall, 520 young female normal-speaking subjects were examined by videostroboscopy for different phonation conditions in the combination of soft, loud, low, and/or high phonation and by voice range profile measurements. According to the videostroboscopic analysis, the subjects were subdivided into four groups: complete closure of the vocal folds already in soft phonation (group 1), closure of the vocal fold with increasing intensity (group 2), persistent closure insufficiencies despite increasing intensity (group 3), and hourglass-shaped closure in subjects with vocal nodules (group 4). Subjects in which the glottal closure could not be evaluated sufficiently were subclassified into group 5 (missing values). Selected criteria of the singing and speaking voice were evaluated and statistically processed according to the mentioned subclassification. Group 1 reached significantly the highest sound pressure levels (SPL max) for the singing voice as well as for the shouting voice. Group 3 showed a limited capacity to increase the intensity of the singing and speaking voice. The results gathered in this study objectify the relationship of insufficient glottal closure and reduced vocal capabilities. As long as no conclusive data on long-term consequences of insufficient glottal closure are available, a prophylactic improvement of the laryngeal situation especially in female professional voice users by voice therapy should be recommended.